Chemistry and our changing world (Prentice Hall . 2nd ed., 1989)
This volume combines complete topical coverage, easy-to-understand explanations, and a focus on problem solving to give readers an appreciation of the excitement of chemistry and to show how chemistry is used in the real, everyday